Complejo deportivo "Fundo Villa" en Chorrillos - Santos Alvarado, María Milagros (2021)
The Sport Complex Fundo Villa is placed between the urhan settlement Buenos Aires de Villa and the urbanization Villa Marina. The emplacement of the project is now a border between this two places, a wall along the limits of the ground which generates physic and also social fragmentation, reinforcing the perception of insecurity and preventing urban and social relations to merge. The main object of the project is to reinforce social interactions through sport, opening the ground to the public to generate activities and opportunities to distract that can become part of the journey of everyone who use it or pass by.